Remuneration and Engagement: A Study of Catholic Educators - Karen Joy Catacutan; Gladys Tumbali (Research Synergy Foundation, 2025)
This study examined the organizational engagement of Catholic educators in relation to a rationalized remuneration system. Conducted across six Catholic Higher Education Institutions in Region II, it employed a mixed-method research design. A survey was administered to 164 college faculty members with at least three years of tenure, selected through stratified random sampling. Focus group discussions complemented the quantitative findings. Results showed that Catholic educators had highly favorable assessments of their remuneration in terms of fairness, effectiveness, and conformity. They were fully engaged in instruction, Christian faith formation, community engagement, and financial management, but demonstrated lower engagement in research activities. A significant relationship was found between educators' perceptions of remuneration and their engagement in instruction, financial management, extension, and Christian faith formation. These findings guided the development of a rationalized remuneration system to enhance organizational engagement. The study has practical implications for Catholic school leaders in improving faculty compensation strategies to enhance engagement and retention.